Cadmium and Trace Elements Toxicity (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint, entitled “Cadmium and Trace Elements Toxicity,” brings together ten high-quality research articles that advance our understanding of the sources, mechanisms, and health impacts of cadmium and trace element exposure. The contributions span multiple disciplines, from molecular toxicology and environmental monitoring to plant science and risk assessment, providing a comprehensive overview of current research in this critical field. The articles address key topics including novel toxicity mechanisms, biomonitoring approaches, protective strategies, and environmental quality criteria.